Biological consequences of radiation-induced DNA damage: relevance to radiotherapy. - Lomax, M; Folkes, L; O'Neill, P (2013)
DNA damage of exposed tumour tissue leading to cell death is one of the detrimental effects of ionising radiation that is exploited, with beneficial consequences, for radiotherapy. The pattern of the discrete energy depositions during passage of the ionising track of radiation defines the spatial distribution of lesions induced in DNA with a fraction of the DNA damage sites containing clusters of lesions, formed over a few nanometres, against a background of endogenously induced individual lesions. These clustered DNA damage sites, which may be considered as a signature of ionising radiation, underlie the deleterious biological consequences of ionising radiation. The concepts developed rely in part on the fact that ionising radiation creates significant levels of clustered DNA damage, including complex double-strand breaks (DSB), to kill tumour cells as clustered damage sites are difficult to repair. This reduced repairability of clustered DNA damage using specific repair pathways is exploitable in radiotherapy for the treatment of cancer. We discuss some potential strategies to enhance radiosensitivity by targeting the repair pathways of radiation-induced clustered damage and complex DNA DSB, through inhibition of specific proteins that are not required in the repair pathways for endogenous damage. The variety and severity of DNA damage from ionising radiation is also influenced by the tumour microenvironment, being especially sensitive to the oxygen status of the cells. For instance, nitric oxide is known to influence the types of damage induced by radiation under hypoxic conditions. A potential strategy based on bioreductive activation of pro-drugs to release nitric oxide is discussed as an approach to deliver nitric oxide to hypoxic tumours during radiotherapy. The ultimate aim of this review is to stimulate thinking on how knowledge of the complexity of radiation-induced DNA damage may contribute to the development of adjuncts to radiotherapy.